A digitally controlled switch mode power supply based on matrix converter - Somnida Ratanapanachote (2018)
High power telecommunication power supply systems consist of a three-phase switch mode rectifier followed by a dc/dc converter to supply loads at -48 V dc. These rectifiers draw significant harmonic currents from the utility, resulting in poor input power factor with high total harmonic distortion (THD). In this paper, a digitally controlled three-phase switch mode power supply based on a matrix converter is proposed for telecommunication applications. In the proposed approach, the matrix converter directly converts the low frequency (50/60 Hz, three-phase) input to a high frequency (10/20 kHz, one-phase) ac output without a dc-link. The output of the matrix converter is then processed via a high frequency isolation transformer to produce -48 V dc. Digital control of the system ensures that the output voltage is regulated and the input currents are of high quality under varying load conditions. Due to the absence of de-link electrolytic capacitors, power density of the proposed rectifier is expected to be higher. Analysis, design example and experimental results are presented from a three-phase 208-V, 1.5-kW laboratory prototype converter. © 2006 IEEE.